Response of tomato to varying levels of fertigation - Rajaseelan Kingsly D (Department of Agronomy, College of Horticulture, 2002)
A field experiment was conducted during 2000-2001 at the Agricultural Research Station, Mannuthy, Thrissur to find out growth and yield as well as water use and nutrient relations of tomato, as influenced by different levels of fertigation i.e. continuous nutrition through drip irrigation. The experiment consisted of combinations of three levels of irrigation (0.3,0.6 and 0.9 PE) through drip system and three levels of fertilizer (100, 50 and 150% recommended dose) supplied through drip irrigation. The fertilizer nutrients were supplied in progressive increments for sixty days and the fertigated treatments were mulched using black HDPE sheet. A control treatment, which received 20 mm surface irrigation through furrow method once in three days along with normal soil application of fertilizer without mulch cover was also included to compare with fertigation treatments. The experiment was laid out at randomised block design with three replications. The tomato CV Shakthi was tried in the experiment. The results revealed that the growth parameters viz., plant height, Leaf Area Index (LAI) and ~eaf Area Duration (LAD) were higher in the fertigated treatments than in the control crop. The respective values were 50.48 cm, 5.60 and 113.4 in case offertigated crops and 48.52 cm, 5.46 and 110.9 for the control crop, when observed at final growth stage. The control crop had a significant rooting pattern with higher vertical length (26.8 cm), lateral length (15 cm) and root dry weight of (8.2 g) than the fertigated treatments which had the respective values of 18.65 cm, 11.00 cm and 3.9 g. The ferigated crop produced maximum fruit set of